The Role of Humans in the Perspective of Islamic Educational Philosophy - Pramono, Bayu; Sirojudin, Rumbang; Muttaqin, Zainal; Supianto, Supianto; Fauzi, Anis (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study discusses the role of human beings in the perspective of Islamic educational philosophy with a qualitative approach to literature study. Based on a literature review, the main findings show that education in Islam has a holistic goal, which includes intellectual, moral, and spiritual development. Al-Farabi and Al-Ghazali's thought emphasizes the importance of balancing worldly and ukhrawi knowledge, as well as moral development as an integral part of education. The study also identifies the relevance of classical thought in the context of modern education and evaluates how these theories can be applied in current Islamic educational practices. The implications of this research include the application of Islamic educational philosophy to form individuals who are not only intelligent, but also have noble character.